ANALISIS PENGGUNAAN BEBERAPA JENIS KEMASAN PLASTIK TERHADAP UMUR SIMPAN SAYUR SELADA (Lactuca sativa L) SELAMA PENYIMPANAN DINGIN - Octavianda I. C. Mamonto; Dr. Ir. Lady. C. Ch. E. Lengkey, MSi; Dr. Ir. Frans. Wenur, MS (COCOS, 2019)
ABSTRACTThe objectives of this study were to analyze the weight loss, texture and colorchanges of lettuce during cold storage and determine the packaging that can be usedto store lettuce with a longer shelf life. The results of this study, lettuce using LDPEand PP type packaging at a temperature of 8.14 oC gave the best results for 9 daysof storage. Lettuce stored at 8.14 oC using LDPE and PP packages gave the smallestpercentage weight loss results, namely 4.48% and 1.03%. The hardness valuepacked with LDPE plastic at the base is 5.51 N, the middle part is 1.18 N, and thehardness value packed with PP plastic at the base is 4.23 N, the middle is 1.32 N.The last day gave the results of the hardness value packed with LDPE plastic at thebase of 8.56 N, the middle part of 1.31 N and the type of PP plastic packaging whichhad a hardness value at the base of 8.81 N, the middle part of 1.87 N with a physicalappearance still fresh and hard and the color changes to yellowish green on theleaves. LDPE and PP plastic packaging gives good results which can be used forstorage of lettuce with a longer shelf life.Keywords: Lettuce, PVC and LDPE packaging, PP